The Impact of Taxes on the Consumption to Income Ratio - Bartkus, Algirdas (Ekonomika, 2017)
This article, in the statistical analysis of possible cointegration relationships among the variables from the expenditure approach to the GDP formula, explains how taxes affect the consumption to income ratio. A causal relationship that defines investment as the leading factor in GDP formation was rearranged and applied for the study of taxation effects under various income levels. The technique that was used for the estimation of taxation effects was based on the deterministic part of causal relationship, though the results must be interpreted very carefully. This analysis demonstrates that, when taken to the extreme, higher taxes have a huge negative effect on consumption and a very small effect on savings; in addition, these effects depend on the level of income. The higher the incomes are, the more deteriorating the effects of taxes on consumption can be observed; therefore, an economy cannot afford a high level of taxes, even when the income level is also high. As taxes have negative effects on consumption and, with lesser extent, on savings, tax-based fiscal consolidation has to be avoided at any cost, and governments should rely on tax-based fiscal consolidation only if no other option is available.
Keywords: Consumption; Savings; Taxes; Granger causality; Cointegration